Genetic and phenotypic parameter on fertility traits of Red Chittagong Cattle in Bangladesh (Bangladesh Veterinarian, 2013)
The fertility of Red Chittagong Cattle (RCC) of Bangladesh was studied using data from 122 animals from four herds. The least squares means of female fertility traits were 1.4 ± 0.1, 72.6 ± 3.6% and 85.0 ± 2.0%, respectively, for number of services per pregnancy, first service pregnancy rate and overall pregnancy rate. The least squares mean of non-return rate to first service of bull was 58.7 ± 5.1%. The factor having a significant effect on female fertility was herd, while parity had no effect. Herd and parity of dam, season of service and sire had no effect on non-return rate to first service of bull. The heritability of fertility traits were very low: values were 0.07 ± 0.04, 0.03 ± 0.04, 0.05 ± 0.04 and 0, respectively, for number of services per pregnancy, first service pregnancy rate, overall pregnancy rate and non-return rate to first service of bull. The corresponding repeatability values were 0.18 ± 0.08, 0.08 ± 0.07, 0.13 ± 0.08 and -0.07 ± 0.02, respectively. This study reveals the fertility to be good. However, better reproductive management may enhance the overall herd fertility of RCC. DOI: http://dx.doi.org/10.3329/bvet.v29i2.14347 Bangl. vet. 2012. Vol. 29, No. 2, 78-89